2016
DOI: 10.1371/journal.pone.0154505
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Dynamics of a Mortality Event among Central African Great Apes

Abstract: In 2006–2007 we observed an unusual mortality event among apes in northern Republic of Congo that, although not diagnostically confirmed, we believe to have been a disease outbreak. In 2007–2011 we conducted ape nest surveys in the region, recording 11,835 G. g. gorilla nests (2,262 groups) and 5,548 P. t. troglodytes nests (2,139 groups). We developed a statistical model to determine likely points of origin of the outbreak to help identify variables associated with disease emergence and spread. We modeled dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…Our review revealed many more road ecology publications from Africa than we expected, with a significant increase in the number of publications since 2006. Most of the publications were from the more affluent and politically stable regions (e.g., southern and East Africa), particularly pre-2006 publications (Drews, 1995;Dean and Milton, 2000), whilst post-2006 publications saw an increase in the number of papers from Central Africa (Hicks et al, 2012;Tompkins et al, 2015;Cameron et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our review revealed many more road ecology publications from Africa than we expected, with a significant increase in the number of publications since 2006. Most of the publications were from the more affluent and politically stable regions (e.g., southern and East Africa), particularly pre-2006 publications (Drews, 1995;Dean and Milton, 2000), whilst post-2006 publications saw an increase in the number of papers from Central Africa (Hicks et al, 2012;Tompkins et al, 2015;Cameron et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of all these factors, great ape populations have experienced a precipitous decline within the last 40 years (Fruth and Hohmann 1996;Walsh et al 2003;Williamson et al 2013). Thus, large-scale conservation measures are needed urgently in order to avoid further decline of great ape populations as well as to mitigate the various threats (Spehar et al 2010;Cameron et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…, Cameron et al. ). Identification of the virus's true reservoir and infection pathways in nature remains important research (Leendertz ).…”
Section: Great Ape Health Monitoring Research and Disease Awarenessmentioning
confidence: 99%
“…Such monitoring has been shown to be a prerequisite for the early detection and effective sampling of suspected cases of EVD (Leendertz et al 2006, Travis et al 2008; laboratory analysis is the only way to confirm Ebola infection. Antibody testing of non-invasively collected great ape samples can show which populations have been exposed to the virus, and surveys to estimate group density and population numbers may provide information about population declines possibly caused by Ebola (Campbell et al 2008, Kouakou et al 2009, Olson et al 2012a,b, Reed et al 2014, Cameron et al 2016). Identification of the virus's true reservoir and infection pathways in nature remains important research (Leendertz 2016).…”
Section: Great Ape Health Monitoring Research and Disease Awarenessmentioning
confidence: 99%